Determinant Factor of Consumers’ Decision Relating to The Purchase of Selection Food Shop - Bernadeta Wahyu Astri Pratita (Manajemen Kreatif Jurnal, 2023)
Consumers’ purchasing decision of a product or service can be affected by several factors. In this research there are 5 factors: product, employee service, culture, price and psychological. The purpose of this study is to determine whether these 5 factors are the factor considered by the customers in purchasing products in the selection food shop (Mie Setan). This research uses quantitative approach with 100 respondents as sample. They were obtained with incidental sampling technique. Data were obtained by using questionnaire instrument. Meanwhile, the technique of data analysis used confirmatory factor analysis. The result show that the most determinant Factor of consumers’ decision purchasing is the product.